Students' Perceptions of Using English Songs for Listening Skill - Wusqo, Urwatul; Wahab, Abdul Aziz; Ferdiyanto, Feri (International Journal of English Education and Linguistics (IJoEEL), 2024)
The aim of this research is to identify, classify, and describe students' perceptions of learning English by using songs for listening skills. Also, it is to Analyze and describe the learning aspects that can improve students' listening skills through listening to English songs. This research used qualitative methods. The researchers collected data from ten students in the sixth semester of English Education Department at Zainul Hasan Genggong Islamic University. The researcher found five perceptions as a result of this study, namely the use of English songs in English learning is fun, not boring, effective learning media, entertaining and improves brain ability. In this study, researchers also found an improvement in students' listening skills, namely, there were fifteen students who felt an improvement in their listening skills